Diversifikasi Pengolahan Jahe Menjadi Produk Awetan - Nami Lestari; Eldha Sampepana; Sitti Nurlina; Tita Sri Palupi (Jurnal Riset Teknologi Industri, 2016)
Ginger ( Zingiber Officinale) is one of spices having many beneficial uses and its potency in East Kalimantan is quite big.  This region produces about2,454.000  tons of  ginger  every  year.  (The  Plantation  Services of  East Kalimantan Province, 2004). The aim of this research is to find an effecient technology for small and madium scale industries to process ginger to become preserved products like instant ginger drinks, candies and syrup. The research looked for the right formulae in processing of instant ginger drinks and ginger syrups and tile right filler substance in making ginger candies. The formula willbe represented in the composition of ginger, sugar and water. Based on organoleptic testing, the best species of ginger made for those products is "elephantginger" and Ihe best composition for making instant ginger products is 750 gram, 1000 gram and 250 ml for "elephant ginger'; sugar and waterrespectively. In addition, the best composition to make ginger syrup is 500 gram and 1000 ml of ..elephant ginger". suqer and water respectively. Lastly. the best filler substance for soft ginger candy is gelatinous flour.